Values Beyond Value? Is Anything Safe from being Subsumed by the Logic of Capitalism? - Skeggs, Beverley (feminists@law, 2013)
<span lang="EN-US" style="font-family: "Cambria","serif"; font-size: 12pt; mso-fareast-font-family: "MS Mincho"; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA; mso-bidi-theme-font: minor-bidi; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin;">There has been a great deal of interest recently in how capital has intervened in almost every area of life, leading some to propose new forms of capital eg ‘emotional capitalism’ (Illouz), and others to suggest that processes of valuation are now the major method for understanding the social world (Arviddson, Adkins and Lury). Whilst, no doubt, capital behaves according to its own logic, finding new lines of flight, converting affects such as sentiment and suffering into value, making multi-culturalism marketable, generating new forms of bio-capital, and making many of our actions subject to the logic of calculation (our writing for instance), I want to explore what is left behind. If we only understand the world from the perspective of the logic of capital does anything remain? I’ve been caught in Bourdieu’s paradox for some time. Is it possible to escape? Are there any values beyond valuation?